Exploring the Influence of Self-Perceived Communication Competence and Communication Apprehension on EFL Learners' Classroom willingness to communicate. Case of Master Two Students at M’sila University. - Nada Erreyhane HELITIM, Dr. Chaouki BOUNAAS (université mohamed boudiaf .m'sila, 2023)
Abstract Given the growing importance of willingness to communicate (WTC) as an individual difference in explaining and predicting second language communicative patterns, there was a need to explore this construct situated within Algerian English as foreign language (EFL) classroom context,along with its two major affective antecedents namely: communication apprehension (CA) and self-perceived communicative competence (SPCC). The current study had three primary objectives.First, it aimed to describe learners' levels of willingness to engage in classroom communication, their apprehension about communication, and their self-assessment of communication competence.In its second objective,the study sought to explore the relationships between these communicative variables. Finally, a multiple regression analysis was conducted a to predict the effect of SPCC and CA on learners’ WTC.to achieve these objectives, a quantitative research design was employed with a self-reported questionnaire as a main data collection tool. The questionnaire was administrated to a random sample of 45 EFL master two’s program learners at M’sila University. The obtained data were analyzed through SPSS version 25. The findings revealed that the participants demonstrated moderate levels for both SPCC and CA, while their overall WTC level was found to be relatively high, Moreover, the correlations analysis revealed a statistically significant positive correlation between learners’ SPCC and their WTC, and a negative correlation between their CA and their WTC.However, The results from the regression analysis revealed that learners’ SPCC was the only predictor of their WTC.In conclusion, The research study ended by discussing theoretical and practical implications that raise awareness among EFL teachers regarding the importance of generating the communicative willingness in learners to actively use language and calling for strategies that reduce their anxiety and enhance their self-confidence regarding their communicative competence as direct predictor of their inclination to engage in frequent L2 communication as a meaningful and effective way for successful language acquisition and proficiency development.
Keywords: Keys words: self -perceived communicative competence, communication apprehension, willingness to communicate , regression analysis .